Decoupling of N and P aggravated upward along food chains in an urban river ecosystem. (February 2023) - An, Shenqun; Yan, Zhengbing; Song, Ying; Fu, Qiang; Ge, Feiyang; Wu, Zehao; An, Wei; Han, Wenxuan
Abstract: Anthropogenic input of nutrient has profoundly influenced water quality and aquatic organisms, however, large and unbalanced nitrogen (N) and phosphorus (P) inputs (decoupling) can lead to a range of ecological health problems such as eutrophication. Whether and how the decoupling varies along the aquatic food chain remains poorly addressed. Here we chose an urban river ecosystem in the cosmopolis region of Beijing, with reclaimed water as the entire replenishment water source over 20 years, to demonstrate the decoupling pattern of N vs P across trophic levels. Results showed that organism C, N and P concentration increased, but N:P ratio decreased upward along the food chains, suggesting that this decoupling of N and P increased as trophic level ascends. Compared with natural freshwater ecosystem, the decoupling of N and P was aggravated in the reclaimed water river. Moreover, the homeostasis of N and P were higher at higher relative to lower trophic levels, and higher in macro-food chain relative to planktonic food chain. This study, for the first time, revealed the increasing decoupling of N vs P upward along the major food chains in an urban aquatic ecosystem, and could improve the understanding of nutrient cycling at the food chain level under human disturbance, and provide useful information for ecological restoration and eutrophication control of urban wetlands replenished with reclaimed water. Graphical abstract: Image 1 Highlights: The decoupling of N and P increased upward along the aquatic food chains. N–P decoupling was aggravated in reclaimed water with unbalanced nutrient input. Both N and P had higher homeostasis at higher relative to lower trophic levels. Macro-food chain showed higher nutrient homeostasis than planktonic food chain.